2021
DOI: 10.3389/fphys.2021.636140
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plyometric Jump Training on Physical Fitness in Amateur and Professional Volleyball: A Meta-Analysis

Abstract: We aimed to examine the effects of plyometric jump training (PJT) on measures of physical fitness in amateur and professional volleyball players. A systematic electronic literature search was carried out in the databases PubMed, MEDLINE, Web of Science, and SCOPUS. Controlled studies including pre-to-post intervention tests of physical fitness and involving healthy volleyball players regardless of age and sex were considered. A random-effects model was used to calculate effect sizes (ES) between intervention a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
41
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 102 publications
(177 reference statements)
5
41
0
6
Order By: Relevance
“…The utilization of the SSC enhances neural and musculotendinous ability to produce maximal force over a short duration (Wang and Zhang, 2016). Regardless of age, gender, sport, and expertise in training, plyometric training consistently results in improved vertical jumping, agility, and sprinting (Andrade et al, 2018;Ramirez-Campillo and Sanchez-Sanchez, 2020;Ramirez-Campillo et al, 2021b). In a systematic review, plyometric training increased power output in 13 of the 16 included studies, with effects ranging from 2 to 31% (Markovic and Mikulic, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of the SSC enhances neural and musculotendinous ability to produce maximal force over a short duration (Wang and Zhang, 2016). Regardless of age, gender, sport, and expertise in training, plyometric training consistently results in improved vertical jumping, agility, and sprinting (Andrade et al, 2018;Ramirez-Campillo and Sanchez-Sanchez, 2020;Ramirez-Campillo et al, 2021b). In a systematic review, plyometric training increased power output in 13 of the 16 included studies, with effects ranging from 2 to 31% (Markovic and Mikulic, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…According to the training principle of specificity, plyometric jump training (PJT) may be an important element in a volleyball player’s regular training schedule [ 4 ]. A systematic review indicated that PJT increased volleyball players’ strength, agility/speed and vertical jump performance [ 5 ], potentially helping players during decisive match scoring point actions (serve, spike, and block).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Davids et al [14] noted that change-of-direction ability represents an important physical trait that should be included in training programs for youth soccer players. Recent review papers and meta-analyses have reported that 8 weeks of bi-weekly plyometric training improved high-intensity physical abilities (e.g., jumping, sprinting, agility) [15][16][17][18]. Previous studies have recommended the incorporation of combined PSSCoD training into the soccer season to improve jumping, sprinting, and change-of-direction ability.…”
Section: Introductionmentioning
confidence: 99%